2018
DOI: 10.29252/jbrms.5.4.22
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of tumors of the head and neck in a 10-year period in Ilam, Iran

Abstract: Introduction: Cancer is one of the five leading causes of death around the world, and head and neck cancer is one of the most common incidences, leading to the death of thousands of people each year. Given the epidemiological importance of head and neck cancers, this study aimed to examine the prevalence of head and neck cancers over a 10-year period in Ilam. Materials and methods: This descriptive study was done using the files of 1106 patients with head and neck lesions who were referred to Imam Khomeini hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…Our research also concluded the same outcome with the <30 age group seen as the most common. 4,9,11,15,16 One of the studies conducted in Iran showed the maximum number of cases in the age group of ≥40 years differing from our analysis. 17 A high number of malignant neoplasms were identified in the age group of 51-60 years which showed that chances of getting malignancy increase with age.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Our research also concluded the same outcome with the <30 age group seen as the most common. 4,9,11,15,16 One of the studies conducted in Iran showed the maximum number of cases in the age group of ≥40 years differing from our analysis. 17 A high number of malignant neoplasms were identified in the age group of 51-60 years which showed that chances of getting malignancy increase with age.…”
Section: Discussioncontrasting
confidence: 82%
“…17,29 In Iran, BCC, and Brazil, mucoepidermoid carcinoma was prevalent in malignant neoplasms respectively. 12,15 The common inflammatory lesion analyzed in this study was reactive lymphadenitis (27%). Among the rest of the lesions, inflammatory polyps (20%) and pyogenic granuloma (17%) were often diagnosed.…”
Section: Discussionmentioning
confidence: 91%